Enjeux environnementaux : quand les « travaux terrains » s’arriment avec l’école secondaire pour le développement d’une écocitoyenneté chez des élèves de 12 à 14 ans en S&T au Québec - Catherine Simard; Ghislain Samson; Émilie Morin; Geneviève Therriault (Éducation et Socialisation)
Faced with environmental challenges affecting ecosystems and biodiversity near Quebec schools, the educational program Opération PAJE proposes an innovative approach to teaching science and technology at the secondary level. Grounded in experiential learning with an emancipatory goal, the program integrates fieldwork into classroom content, encouraging students to design practical solutions to locally identified environmental issues. This study investigates the educational initiative as a means of actively engaging youth in addressing environmental problems within their communities. Findings indicate that implementing projects closely linked to local territories enhances the meaningfulness of school learning, fostering students' sense of pride and responsibility as they witness the positive impacts of their actions. Observed outcomes include cognitive, affective, and behavioral learning, such as identifying biodiversity, experiencing interconnectedness with nature, and feeling empowered to support and care for biodiversity.